PROFESIONALISME GURU PENDIDIKAN KRISTEN BAGI ANAK USIA DINI - Refni fajar Wati Zega; Philipus Sunardi; Lily Peggy Kawatu (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
A profession is a job based on being an educator in a particular field of expertise who, after being trained first, will become a professional educator who is an expert in his field and is able to master and strive to provide the latest and other innovations that are good for the community. There are many problems faced by an educator in conveying learning to students, in this case, young children. First, you have to determine the teaching techniques that will be taught and you have to understand how early childhood development and growth occurs. This certainly introduces a learning approach process that is relevant for early childhood, not just theory but also a teacher's tendency to emphasize knowledge and skills both in learning theory and in forming the character of early childhood as well as providing stimulation and encouraging students to grow spiritually and knowledge simultaneously.